The Teaching Model of Pare Arabic Village through Phonetic and Memorization Methods for Learning Speaking Skills - Gina Alfiyani; Amin Nasir (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Speaking skills represent a crucial aspect of Arabic language learning, demanding mastery of vocabulary, grammatical structures, pronunciation, and learner confidence. However, many students in Islamic schools, including those at MTs Al-Multazam Mojokerto, still struggle to use Arabic actively and spontaneously in communication. To address this issue, the madrasah collaborated with teachers from Kampung Arab Pare, who implemented phonetic drilling and memorization (Al-Kharfi wa Al-Khafdzi) methods. These methods are known to effectively enhance students’ vocabulary retention, pronunciation accuracy, fluency, and self-confidence in speaking Arabic. This study aims to investigate the role of Kampung Arab Pare teachers in improving students’ maharotul kalam (speaking skills), focusing on teaching effectiveness, environmental support, and the challenges encountered during implementation. Using a descriptive qualitative approach, the research collected data through observation, interviews, and documentation, which were analyzed through reduction, presentation, and conclusion drawing. The findings reveal that the integration of the Pare methods fosters a more interactive and motivating learning atmosphere, significantly improving students’ oral competence. This study contributes to the advancement of communicative Arabic language teaching and provides valuable insights for educational institutions seeking to design learning environments that promote active and confident Arabic communication.